Heat transfer of ag-Al2O3/Water hybrid nanofluid on a stagnation point flow over a stretching sheet with newtonian heating - Muhammad Khairul Anuar, Mohamed; Ong, Huei Ruey; Alkasasbeh, Hamzah Taha; Mohd Zuki, Salleh (IOP Publishing, 2020)
The present study investigated the flow and heat transfer at a stagnation point past a stretching sheet. The premium silver nanoparticles Ag and economic alumina nanoparticles Al2O3 suspended in water to form Ag-Al2O3/Water hybrid nanofluid are numerically examined. The analysis started with transforming the mathematical model which is in non-linear partial differential equations to a more convenient form by similarity transformation approach before being solved numerically using the Runge-Kutta-Fehlberg (RKF45) method. The characteristics and effects of the stretching parameter, conjugate parameter and the nanoparticle volume fraction for Al2O3 and Ag on the variation of wall temperature, heat transfer coefficient and reduced skin friction coefficient are analyzed and discussed.